Autism spectrum disorder, social anxiety and obsessive–compulsive disorders: beyond the comorbidity - Liliana Dell’Osso; Giulia Amatori; Chiara Bonelli; Benedetta Nardi; Enrico Massimetti; Ivan Mirko Cremone; Stefano Pini; Barbara Carpita (BMC Psychiatry)
Abstract Objective Autism spectrum disorder (ASD) is characterized by high rates of comorbidity with other mental disorders, including anxiety disorders and obsessive–compulsive disorder. Beyond a mere concept of comorbidity, recent literature is speculating the existence of a neurodevelopmental nature of such mental disorders. The aim of the study is to investigate the distribution of social-phobic, obsessive–compulsive and panic-agoraphobic traits within a sample of individuals with ASD, social anxiety disorder (SAD), obsessive–compulsive disorder (OCD) and panic disorder (PD). Methods 40 participants with ASD, 40 with SAD, 40 with OCD, 40 with PD and 50 HC were assessed with the Social Anxiety Spectrum—Short Version (SHY-SV) questionnaire, the Obsessive—Compulsive Spectrum—Short Version (OBS-SV) questionnaire and the Panic Agoraphobic Spectrum—Short Version (PAS-SV) questionnaire. Statistical analyses included Kruskal–Wallis test and Chi-square test. Results When analyzing SHY-SV scores, the SAD group obtained the highest scores, with individuals with ASD following closely, significantly surpassing the scores of the remaining diagnostic groups. In the examination of OBS-SV questionnaire scores, individuals with ASD once again secured the second-highest scores, trailing only the OCD group. These scores were notably higher than those of both the PD group and healthy controls. In the analysis of PAS-SV scores, the ASD group once again achieved the highest scores after the PD individuals, although this time the difference was not statistically significant compared to the other diagnostic groups. Discussion These findings highlight the central role of the autism spectrum in SAD and OCD diagnoses. They provide support for the hypotheses of a neurodevelopmental basis for social anxiety and OCD, contributing to the growing body of evidence supporting a dimensional and interconnected view of mental health conditions.